Peran Kualitas Pelayanan dengan Aplikasi PLN Mobile dalam Meningkatkan Kepuasan Pelanggan - Shintya Yuliana; Nor Norisanti; Faizal Mulia (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study is to study the quality of service using the PLN Mobile Application in increasing customer satisfaction with quantitative methods at PT. PLN (Persero) Rayon Cikembar, Sukabumi Regency. The research method used is a quantitative method. The analysis technique used is the validity test, reliability test, simple linear regression analysis, including the coefficient of determination test and hypothesis testing using partial testing (t test). The results of the study, obtained an R number of 0.232 in the category 0.00 - 0.199, which means a low relationship between service quality and customer satisfaction. Conclusions, each Service Quality (X) variable in this study can represent each variable and can be used by future researchers. Keywords: Service Quality, Customer Satisfaction.